Value Relevance of Corporate Tax Avoidance in Listed Consumer Goods Firms in Nigeria - Daniya, Abdulazeez Adeiza; Dandago, Kabiru Isa; Muhammad, Muhammad Liman (Universitas Negeri Semarang, 2024)
Purpose : In the last couple of years, the Nigerian government has vigorously increased its revenue base through economic diversification with an unprecedented focus on taxation. It constitutes an economic burden on the manufacturing companies that pay different types of tax. Therefore, they are left with no option but to optimize their tax avoidance effort to continue to create value for the shareholders. Therefore, this study evaluates the value relevance of corporate tax avoidance in listed consumer goods firms for 12 years (2009-2020). Method : Both Tax Saving (T.S.) and Tax Shelter (TSh) were used as proxies for tax avoidance, while Tabin’s Q (T.Q.) was used to measure value. The study employs correlational research design because it allows the relationship between quantitative data to be established, and the quantitative data from the annual reports and accounts of the firms were analyzed using fixed effect regression, having carried out some robustness tests such as normality, VIF, Heteroskedasticity, and Hausman specification tests respectively.Findings : The study revealed that increased tax savings led to an insignificant reduction in firm value. However, an increase in tax shelter propensity and firm age led to a significant improvement in the value of the firms. Consequently, the study found no empirical evidence to reject the first hypothesis, while the second hypothesis was rejected.Novelty : Despite the paucity of studies in Nigeria, there is no available study in Nigeria to the best of our knowledge that used tax shelter as a measure of tax avoidance, which makes this study novel and different from other few available Nigerian studies.